Comparative Analysis of E-Commerce Sales of Halal-Labeled Products in Muslim Majority and Minority Countries - Khirana Dwicahyo; Chanifah Indah Ratnasari (International Journal of Social Science and Religion (IJSSR), 2023)
E-commerce is an alternative for individuals to look for and purchase things. Unfortunately, despite its importance in digital market connectedness, e-commerce has not played a significant role in the continuity of the halal market. This study aims to look at the differences in halal product sales in Muslim majority and minority countries, which can stimulate the availability of halal products on e-commerce and increase halal product exports, as well as make it easier for Muslim communities to buy halal products. There was no previous research on a similar topic, notably one that specifically explored the sale of halal products through e-commerce. Halal-labeled product data was taken from Lazada e-commerce using web scraping (using the Selenium package in the Python programming language), which was then carried out by Kruskal-Wallis analysis. According to the findings, the average sales of halal products in Indonesia, Malaysia, Singapore, and Malaysia varies significantly. However, in the pairwise or combination test comparing groups of countries, it was discovered that the average sales of halal products in Indonesia and Singapore were identical.